Investigation of biological activities of various 1,2,3-triazole compounds: Their effects on cholinesterase enzymes, determination of antioxidant capacity and antimicrobial activity - Almaz, Züleyha (Wiley, 2022)
1,2,3-triazoles are pharmaceutically significant compounds that have attracted recent interest from medicinal chemists because of their important biological activities. Addressed herein, some 1,2,3-triazoles were synthesized to investigate the inhibitory activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes, antioxidant capacity, and antimicrobial effect. The antioxidant profile of 1,2,3-triazoles determined by varied bioanalytical antioxidant methods, including 2,2 '-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS(.+)), 1,1-diphenyl-2-picrylhydrazil (DPPH center dot), cupric ion (Cu2+) and ferric ion (Fe3+) ascorbic acid, butylated hydroxyanisole (BHA), and butylated hydroxytoluene (BHT) were used as the standard compounds. In addition, the antibacterial and antifungal activities of these compounds were investigated against seven bacteria and three fungal species using the hollow agar method. As a result of these studies, it was determined that compound 4 showed the best antimicrobial activity and antioxidant activity close to the standards. Inhibitory effects and kinetic studies of these molecules on cholinesterase enzymes were performed. According to the results obtained, compound 4 showed stronger AChE inhibition and compound 3 stronger BChE inhibition compared to other compounds. In kinetic studies, it was found that AChE showed noncompetitive inhibition by compound 4, and BChE showed competitive inhibition by compound 3.
Keywords: Antibacterial; anticholinesterase; antifungal; antioxidant; Molecular Docking; Anticancer Activity; Derivatives